Talk on the End of the World at Mahabbah Carnival 10.0 - Nor Sa’adatul Afzan, Jusoh (2019)
Muslims have always been reminded about Dajal, the evil figure that will appeat towards the end of the world and power to manupulate people, and that every Prophet and Rasul knows about Dajal.